2022
DOI: 10.3390/biology11030409
|View full text |Cite
|
Sign up to set email alerts
|

The Phylodynamic and Spread of the Invasive Asian Malaria Vectors, Anopheles stephensi, in Sudan

Abstract: Anopheles stephensi is an invasive Asian malaria vector that initially emerged in Africa in 2012 and was reported in Sudan in 2019. We investigated the distribution and population structure of An. stephensi throughout Sudan by using sequencing and molecular tools. We confirmed the presence of An. stephensi in eight border-states, identifying both natural and human-made breeding sites. Our analysis revealed the presence of 20 haplotypes with different distributions per state. This study revealed a countrywide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
(119 reference statements)
0
21
0
Order By: Relevance
“…Nonetheless, limited studies showed that at least two strains of CCHFV (Sudan Al-fulah 2018, and Sudan Abyei 2009) are circulating in Sudan and were involved in previous separate epidemics [ 33 , 37 ]. Recent studies about the emergence of the invasive Asian malaria vector Anopheles stephensi in the country have highlighted the importance of using molecular and genomics sequencing tools for the early detection and monitoring of the disease’s vector dynamics [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, limited studies showed that at least two strains of CCHFV (Sudan Al-fulah 2018, and Sudan Abyei 2009) are circulating in Sudan and were involved in previous separate epidemics [ 33 , 37 ]. Recent studies about the emergence of the invasive Asian malaria vector Anopheles stephensi in the country have highlighted the importance of using molecular and genomics sequencing tools for the early detection and monitoring of the disease’s vector dynamics [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported in 2012 that the annual cost of zoonotic and food-borne diseases is approximately USD 84 billion, 60% of which is due to the cost of human health, 30% is attributed to animal mortality, and 10% to lost productivity [ 44 ]. Arboviral diseases pose a severe socioeconomic burden, particularly on poor farm-depending communities, yet those of CCHF are understudied [ 6 , 22 , 37 , 38 ]. Therefore, social studies investigating the societal impacts of CCHF and its outbreaks are needed to quantify the cost-effectiveness of prevention and control measures.…”
Section: Discussionmentioning
confidence: 99%
“…stephensi is rapidly spreading within Africa. Though this data is limited to national borders, the extensive geographical spread in Ethiopia [ 19 , 31 ] and Sudan [ 5 ] are evidence that the vector species could already have domiciled in many sites distant from the initial port of entry. In the case of Sudan, where An.…”
Section: Understanding and Responding To The Threatmentioning
confidence: 99%
“…Subsequent investigations have confirmed the presence of the vector species in multiple sites in Ethiopia [ 2 ], Somalia [ 3 ] and Sudan, where one of the latest discoveries happened serendipitously during an urban search for culicines [ 4 ]. More recent surveys in Sudan have confirmed extensive geographical spread of the vector, including observations in districts bordering six other countries without any prior evidence of the species [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main malaria vectors in Africa belong to three major groups of vectors, the Anopheles gambiae complex, the Anopheles funestus group, and the Anopheles nili complex [ 15 , 16 ]. However, recently the invasive Asian malaria vector, Anopheles stephensi has emerged in the Horn of Africa region and is rapidly spreading in the area [ 17 – 20 ].…”
Section: Introductionmentioning
confidence: 99%